A Comparison of Facial Color Pattern and Gazing Behavior in Canid Species Suggests Gaze Communication in Gray Wolves (Canis lupus) - Ueda, Sayoko; Kumagai, Gaku; Otaki, Yusuke; Yamaguchi, Shinya; Kohshima, Shiro (PLOS ONE, 2014)
As facial color pattern around the eyes has been suggested to serve various adaptive functions related to the gaze signal, we compared the patterns among 25 canid species, focusing on the gaze signal, to estimate the function of facial color pattern in these species. The facial color patterns of the studied species could be categorized into the following three types based on contrast indices relating to the gaze signal: A-type (both pupil position in the eye outline and eye position in the face are clear), B-type (only the eye position is clear), and C-type (both the pupil and eye position are unclear). A-type faces with light-colored irises were observed in most studied species of the wolf-like clade and some of the red fox-like clade. A-type faces tended to be observed in species living in family groups all year-round, whereas B-type faces tended to be seen in solo/pair-living species. The duration of gazing behavior during which the facial gaze-signal is displayed to the other individual was longest in gray wolves with typical A-type faces, of intermediate length in fennec foxes with typical B-type faces, and shortest in bush dogs with typical C-type faces. These results suggest that the facial color pattern of canid species is related to their gaze communication and that canids with A-type faces, especially gray wolves, use the gaze signal in conspecific communication.